Đặt \(\frac{a}{b}=\frac{c}{d}=k\)\(\left(k\in Z\right)\)
\(\Rightarrow a=bk,c=dk\)
Có :
\(\left(\frac{a+b}{c+d}\right)^3=\frac{\left(bk+b\right)^3}{\left(dk+d\right)^3}=\frac{\left[b\left(k+1\right)\right]^3}{\left[d\left(k+1\right)\right]^3}=\frac{b^3\left(k+1\right)^3}{d^3\left(k+1\right)^3}=\frac{b^3}{d^3}\)
\(\frac{a^3+b^3}{c^3+d^3}=\frac{\left(bk\right)^3+b^3}{\left(dk\right)^3+d^3}=\frac{b^3k^3+b^3}{d^3k^3+d^3}=\frac{b^3\left(k^3+1\right)}{d^3\left(k^3+1\right)}=\frac{b^3}{d^3}\)
\(\Rightarrow\left(\frac{a+b}{c+d}\right)^3=\frac{a^3+b^3}{c^3+d^3}\left(=\frac{b^3}{d^3}\right)\)
Vậy ...
a/b = c/d =K ( K thuộc N* )
a = bK
c = dK
thay vào 2 cái cần so sanh đó là ok
k cho mik nha
Ta có:
a/b=c/d => a/c=b/d = (a+b)/(c+d)=> (a/c)3=(b/d)3=(\(\frac{a+b}{c+d}\) )3 (1)Lại có: (a/c)3=(b/d)3 = a3/c3 = b3/d3 = \(\frac{a^3+b^3}{c^3+d^3}\)
Vậy (\(\frac{a+b}{c+d}\) )3 = \(\frac{a^3+b^3}{c^3+d^3}\)